Two-Dimensional Manipulation in Mid-Air Using a Single Transducer Acoustic Levitator - Harri Wijaya; Kourosh Latifi; Quan Zhou (Micromachines, 2019)
We report a single transducer acoustic levitator capable of manipulating objects in two-dimensions. The levitator consists of a centrally actuated vibrating plate and a flat reflector. We show that the levitation position of the object depends not only on the vibration frequency, but also on the tilting angle between the plate and the reflector. Additionally, new levitation positions can be created by actuating the plate with a composite signal of two frequencies using frequency switching. Based on recorded levitation positions, such single transducer acoustic levitator can manipulate a cluster of levitated microspheres in predefined trajectories, with mean position error of 155 ± 84 µm.